2015
DOI: 10.21157/j.med.vet..v9i2.3810
|View full text |Cite
|
Sign up to set email alerts
|

JUMLAH ERITROSIT DAN NILAI HEMATOKRIT SAPI ACEH DAN SAPI BALI DI KECAMATAN LEUMBAH SEULAWAH KABUPATEN ACEH BESAR (Total Erythrocytes Count and Haematocrit Value of Aceh and Bali Cattle in Leumbah Seulawah, Aceh Besar)

Abstract: The aim of this research was to find out total erythrocytes count and hematocrit value of aceh and bali cattle in Leumbah Seulawah, Aceh Besar. Ten aceh cattle (5 males and 5 females with the age of 2.5-3.0 years) and ten bali cattle (5 males and 5 females aged 2.5-3.0 years) from Leumbah Seulawah, Aceh Besar were used in this research. Blood samples approximately 3 cc were collected by venoject through jugular vein. Erythrocyte counts were performed using a hemocytometer and hematocrit value were performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 2 publications
3
6
2
7
Order By: Relevance
“…Perbedaan hasil penelitian dengan penelitian Adam et al (2015) tersebut diduga lebih dipengaruhi oleh perbedaan pakan yang diujicobakan. Faktor pakan terutama konsumsi energi sangat menentukan tinggi rendahnya kandungan eritrosit.…”
Section: Hasil Dan Pembahasan 31 Pengaruh Perlakuan Terhadap Kandungunclassified
See 1 more Smart Citation
“…Perbedaan hasil penelitian dengan penelitian Adam et al (2015) tersebut diduga lebih dipengaruhi oleh perbedaan pakan yang diujicobakan. Faktor pakan terutama konsumsi energi sangat menentukan tinggi rendahnya kandungan eritrosit.…”
Section: Hasil Dan Pembahasan 31 Pengaruh Perlakuan Terhadap Kandungunclassified
“…Faktor pakan terutama konsumsi energi sangat menentukan tinggi rendahnya kandungan eritrosit. Dalam laporan-laporan di atas, kandungan eritrosit hasil penelitian Adam et al (2015) lebih rendah karena hanya menggunakan hijauan 100%, tanpa konsentrat dalam pakan sehingga berdampak pula pada rendahnya karbohidrat mudah tercerna yang dikonsumsi ternak. Konsentrat merupakan sumber energi yang mudah tercerna, sehingga produksi asam propionat yang merupakan prekursor eritrosit akan lebih tinggi.…”
Section: Hasil Dan Pembahasan 31 Pengaruh Perlakuan Terhadap Kandungunclassified
“…Analysis of variance result showed that the synchronized estrus (PGF2α-PGF2α) and synchronized ovulation (PGF2α-GnRH-PGF2α) did not significantly affect (P>0.05) the concentration of erythrocyte, leucocyte, and hemoglobin. Sufficient nutrition in feed would result in a normal level of total erythrocyte within the higher normal range of cow blood (Adam et al, 2015). Also, Roland et al (2014) stated that total leucocyte plays a role in Body defense mechanism, and leucocyte performance would increase in handling viral infection, food poisoning, anaphylactic shock, and dysfunction central nervous system.…”
Section: Hematological Statusmentioning
confidence: 99%
“…Hemoglobin (Hb) value is significantly affected by nutrition sufficiency in the cattle, especially protein as the material for hemoglobin synthesis (Wardayanto, 2004). Meanwhile, Adam et al (2015) stated that nutrition factors play a role in the concentration of hemoglobin in cowsthe more fulfilled the nutrition, the higher the normal range of hemoglobin in the blood. Furthermore, Santosa et al (2014) stated that the increasing demand for O 2 is required to maintain an intensive energy metabolism when the cattle are experiencing distress.…”
Section: Hematological Statusmentioning
confidence: 99%
See 1 more Smart Citation